INOVASI DIGITAL: MENINGKATKAN KUALITAS LAYANAN PUBLIK MELALUI APLIKASI PDAMINFO - Akib, Karmila; Rilfayanti Thomassawa (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aims to determine water account payment services through the pdamINFO application.). The method used in this study is a qualitative method with data collection techniques through observation and interviews and analysis is carried out through reduction, data presentation, verification and conclusions. The results showed that the online water bill payment service at PDAM Poso Regency still could not meet all the New Public Service (NPS) service indicators stated by Carlson and Schwarz optimally. Of the 8 (eight) existing indicators, 3 (three) of them are: Convenience, personal attention and fiscal responsibility has not been maximized. The supporting factors for this online water bill payment service are the accuracy and and many choices of payment systems provided. While the inhibiting factors are the behavior of customers who feel unsatisfied if they do not come to pay at the PDAM counter, internet networks in some service areas that are still unstable and socialization that is still not carried out.